2017
DOI: 10.1016/j.sleep.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of restless legs syndrome and associated factors in an otherwise healthy population: results from the Danish Blood Donor Study

Abstract: RLS is a frequent disorder in otherwise healthy individuals. The associations discovered in this study can be utilized in preventing or reducing RLS symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 35 publications
5
48
0
Order By: Relevance
“…The main finding of our study is consistent with other population‐based studies that also found no association between RLS and measures of iron stores (Benediktsdottir et al, ; Berger et al, ; Didriksen et al, ; Lillo‐Triguero et al, ). We extend those findings by showing a lack of association in young adults.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The main finding of our study is consistent with other population‐based studies that also found no association between RLS and measures of iron stores (Benediktsdottir et al, ; Berger et al, ; Didriksen et al, ; Lillo‐Triguero et al, ). We extend those findings by showing a lack of association in young adults.…”
Section: Discussionsupporting
confidence: 92%
“…In children, it has been reported that the frequency of RLS is higher if ferritin levels are < 50 µg L −1 (Halac et al, 2015), and that low serum ferritin may contribute to the severity of symptoms (Picchietti & Picchietti, 2010). However, other studies have failed to show associations between measures of iron stores and RLS (Benediktsdottir et al, 2010;Berger et al, 2002;Didriksen et al, 2017;Lillo-Triguero, Castillo-Rueda, Valdés-Gross, Guillem-Mesado, & Río-Villegas, 2016), and a systematic review from 2012 assessing six studies did not find sufficient evidence to determine whether iron therapy is beneficial for the treatment of RLS (Trotti, Bhadriraju, & Becker, 2012). It remains unclear if serum ferritin is a risk marker for RLS or a predictor for RLS severity.…”
Section: Introductionmentioning
confidence: 99%
“…The CH-RLSq was validated previously in one population survey [30] and adopted in several population-based studies [31,33,34], as it has considerable diagnostic accuracy [35]. For our study, the original English version of the questionnaire was translated into Korean.…”
Section: Diagnosis Of Rlsmentioning
confidence: 99%
“…Another recent study showed no association of RLS with a reduced ferritin level (for <30 ng/mL and < 40 ng/mL) in neither female donors (odds ratio [OR], 1.14; 95% confidence interval [CI], 0.77‐1.70) nor male donors (OR, 0.79; 95% CI, 0.29–2.20) . The authors did observe that there was a lower mean ferritin level among donors with RLS than donors without RLS (p = 0.02), and that the risk of RLS was higher in female than male donors (Table ); however, no association between RLS and blood donation intensity was found …”
Section: Resultsmentioning
confidence: 94%
“…RLS was measured in nine studies, using several validated questionnaires: the RLS diagnostic index questionnaire, the Cambridge‐Hopkins ascertainment questionnaire for RLS (CH‐RLSq), questionnaire of the International RLS study group and also self‐developed not validated questionnaires or interviews (Table ) …”
Section: Resultsmentioning
confidence: 99%